Investasi Kesehatan dan Gizi di Masa 8000 Hari Pertama Kehidupan dengan Pendidikan Gizi dan Pelayanan Kesehatan Di Indonesia : Literature Review - Sarah Renyoet, Brigitte; Rae, Alfarysthi Elin; Dary (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2024)
The nutrition program by applying the concept of First 1000 days of life has not given maximum results, so the concept of First 8000 days of life appears. The First 8000 days of life concept covers life from 0 months to 21 year olds. The concept of First 8000 days of life is proven to have an impact on neuro-cognitive development that is very effective at that age and affects the health and human resources of future generations. The purpose of this study was to identify or analyze health and nutrition investments in First 8000 days of life.The Method used is literature by obtaining references from PubMed, Lancet, Google Scholar. The literature obtained was selected by paying attention to exclusion criteria whitch were seen from several things such as inappropriate topics and thriugh identifying abstacts that were not appropriate to problems related to the first 8000 days of life and interventions through health facilities and nutrition education. The results of this study indicated that health investment during the First 8000 days of life period is important and with supporting factors, namely health and nutrition education and health services, this program will run optimally. However, it is known that health and nutrition education and health services in Indonesia have not run optimally. The conclusion is that the investment of First 8000 days of life in children and adolescents is very important for the future, but must be supported by health and nutrition education and adequate health services through fully available health facilities.